ANALISIS EFEKTIFITAS PEMBELAJARAN SENI BUDAYA DAN KETERAMPILAN DI SD NEGERI 14 SUKAJADI KOTA PEKANBARU - Widya Pratika Sari; Zariul Antosa; Eddy Noviana (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract. This Research aim to the execution of learning related to the preparation teaching, execution of learning, and learning evaluation. This research started from July 2013 in SDN 14 Sukajadi Pekanbaru. The study of Cultural Art and Skill SDN14 Sukajadi Pekanbaru shared to grow up the creativity energy, and energy of appreciation. With make-up of the understanding of the components could increase the attitude of creativity, self-supporting productive, and also can develop the ability of student thingking. This research was qualitative descriptive. The teaching of collection data was observation technique, equate( documentation and questioner) covered the preparation of learning, execution of learning and learning evaluation. The technique of data analyses covered to collecting data, data verification, data tribulation, and process data. Data-Processing from all components exist in score analysis result of equate to the overall of teacher [at] meeting of I get score 3,075, meeting of II 3,123, meeting of III 3,12 and meeting of IV 3,075 and to the overall of result of equate analysis got Effective category, while data of score analysis result of observation to the overall of teacher [at] meeting of I 1,96, meeting of II 1,90, meeting of III 1, 85, meeting of IV 1,85 and to the overall of result of observation analysis got Less effective category. From the data above can be concluded the teacher were not executed the learning yet become the effective learning. Keyword : Efektifitas, Study of Cultural Art and Skill